2017
DOI: 10.5194/soil-3-1-2017
|View full text |Cite
|
Sign up to set email alerts
|

Greater soil carbon stocks and faster turnover rates with increasing agricultural productivity

Abstract: Abstract. Devising agricultural management schemes that enhance food security and soil carbon levels is a high priority for many nations. However, the coupling between agricultural productivity, soil carbon stocks and organic matter turnover rates is still unclear. Archived soil samples from four decades of a long-term crop rotation trial were analyzed for soil organic matter (SOM) cycling-relevant properties: C and N content, bulk composition by nuclear magnetic resonance (NMR) spectroscopy, amino sugar conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 60 publications
(75 reference statements)
3
22
0
Order By: Relevance
“…, Sanderman et al. ). In some cases, however, lower total C input in one cropping system corresponds to higher SOC (Gregorich et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Sanderman et al. ). In some cases, however, lower total C input in one cropping system corresponds to higher SOC (Gregorich et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis with strong acid has been shown to isolate SOM that is consistently hundreds to thousands of years older than the bulk SOM (Paul et al, 2001). Biological fractionation involves the modeling of mass loss or CO 2 evolution during a laboratory incubation experiment (Grandy and Robertson, 2007;Schädel et al, 2013). Baldock et al (2013), recognizing that fire-derived pryogenic carbon (PyC) has distinct properties from plant or microbial products, combined physical size fractionation with the use of solid-state 13 C nuclear magnetic resonance spectroscopy to mathematically isolate the PyC fraction from each size fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Typical of the results obtained using this approach, Sanderman et al . ( 4 ) found that bulk SOC turnover rates varied from 30 to 40 years in low-productivity crop-fallow system to under 10 years under a highly productive pasture for the same soil in a Mediterranean climate.…”
mentioning
confidence: 99%
“…But multipool modeling and chemical fraction methods reveal that there is also a highly resistant fraction of SOC that can be up to a few thousand years old ( 6 ). This highly resistant fraction can comprise 20 to 60% of the SOC ( 4 , 6 ), suggesting that this carbon was incorporated into the soil under a different climate than found today but the relevant paleoclimate period should be at most 2000 years before present.…”
mentioning
confidence: 99%